Leishmania (L.) infantum chagasi isolated from skin lesions of patients affected by non-ulcerated cutaneous leishmaniasis lead to visceral lesion in hamsters. (April 2023) - Araujo Flores, Gabriela V.; Sandoval Pacheco, Carmen M.; Ferreira, Aurea F.; Tomokane, Thaise Yumie; Nunes, Juliana B.; Colombo, Fabio A.; Sosa-Ochoa, Wilfredo H.; Zúniga, Concepción; Silveira, Fernando T.; Corbett, Carlos E.P.; Laurenti, Márcia D.
Abstract: In Central America, Leishmania ( L .) infantum chagasi infection causes visceral leishmaniasis (VL) and non-ulcerated cutaneous leishmaniasis (NUCL). The aim of the present study was to evaluate the course of an experimental infection in hamsters caused by L . ( L .) infantum chagasi isolated from patients affected by NUCL compared with a strain isolated from a patient with VL. Stationary phase parasites in culture were inoculated through subcutaneous and intraperitoneal routes in hamsters. Following the post-infection times, a histopathological study, parasite load and cytokine determination in skin from the cutaneous inoculation site and viscera were performed. Animals subcutaneously infected with the different strains did not develop macroscopic lesions at the inoculation site, and the histopathological changes in the dermis were very slight. Regarding the histopathological study of the viscera, we observed the portal mononuclear inflammatory infiltrate, the presence of nodules in the hepatic parenchyma and the proliferation of macrophages in the spleen, which increased over the infection course. Overall, the parasite load in the liver and spleen and in the total IgG titres in the sera of infected hamster showed an increase with the time of infection, regardless of the route of inoculation. Regarding cellular immunity, we did not observe an increase or decrease in pro- and anti-inflammatory cytokines compared to the healthy control, except for IL-10, which was evident in the infected animals. The data showed that strains isolated from NUCL cause visceral lesions in the hamsters regardless of the route of inoculation, and they were similar to parasites isolated from VL humans. Graphical abstract: Unlabelled Image Highlights: Strains isolated from LV and NUCL cause visceral disease in hamster. Parasitism increases with time of infection regardless of the inoculation route. Total IgG titers increase with the time of infection. Cellular immunity shows to be weak with discreet presence of IL-10.